1989
DOI: 10.1111/j.1365-2125.1989.tb05352.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of caffeine and its dimethylxanthine metabolites in patients with chronic liver disease.

Abstract: 1. Serum and salivary concentrations of caffeine (1,3,7‐ trimethylxanthine) and its dimethylxanthine metabolites were measured in 10 healthy control subjects and in 19 patients with cirrhosis, for up to 96 h following a 400 mg oral caffeine load. 2. Serum and salivary caffeine concentrations correlated significantly (r = 0.954; P less than 0.001) and no significant differences were observed in the pharmacokinetic data derived from the respective concentration‐time curves. 3. In the control subjects, basal sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0
4

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 21 publications
5
15
0
4
Order By: Relevance
“…The childpugh classification adopted in the present study is also similar to that used by N.R. Scott et al 15 in 1989, their study also showed a significant correlation (p < 0.001) between childpugh score of severity of liver disease and salivary caffeine clearance values. It is also evident from the results that salivary caffeine concentration in patients (study group) at 0 h, i.e.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The childpugh classification adopted in the present study is also similar to that used by N.R. Scott et al 15 in 1989, their study also showed a significant correlation (p < 0.001) between childpugh score of severity of liver disease and salivary caffeine clearance values. It is also evident from the results that salivary caffeine concentration in patients (study group) at 0 h, i.e.…”
Section: Discussionsupporting
confidence: 84%
“…1,5 However saliva is emerging as efficient and feasible diagnostic fluid for many diseases and also being popular among patients and clinicians due to easy collection and less chances of cross contamination and can be used as sample for the study of larger group like country surveys. Saliva has been proposed as suitable diagnostic fluid for caffeine clearance assessment which is substantiated by a number of studies that confirmed an excellent correlation between caffeine elimination in saliva and liver function 14,15,16 In spite of these encouraging studies, the caffeine clearance test from saliva sample is not popular in clinical practice. This warrants further study to assess its feasibility as non invasive diagnostic modality for quantitative assessment of liver function and find out the possible shortcomings which is hindering its popularity.…”
Section: 10mentioning
confidence: 99%
“…Participants were instructed not to eat or drink anything (with the exception of water) after 9:00 p.m. the night before a test session and not to use any over-the-counter medications or herbal supplements 24 h prior to testing. A 12-h abstinence period is thought to be a sufficient wash-out period to attenuate the effects of earlier caffeine consumption, given that the mean plasma and elimination half-life of caffeine ranges from 3 to 10 h (Blanchard and Sawers, 1983; Scott et al, 1989; Nehlig et al, 1992a). Test sessions began between 7:00 and 9:30 a.m.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment order was counterbalanced across participants using a complete Latin square. Participants were tested during morning sessions following a 12 h fast, which is thought to be a sufficient wash-out period to attenuate the effects of earlier caffeine and theanine consumption, particularly given that the mean plasma elimination half-life ranges from 3 to 10 h in caffeine (Blanchard and Sawers 1983;Nehlig et al 1992;Scott et al 1989) and from 65 to 75 min in theanine (Scheid et al 2012;van der Pijl et al 2010). Participants were further instructed not to use any over-the-counter medications or herbal supplements for 24 h prior to testing.…”
Section: Designmentioning
confidence: 99%